2008
DOI: 10.1021/jp710484b
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Methanol Decomposition on the CeO2(110) Surface

Abstract: Methanol decomposition on the stoichiometric CeO 2 (110) surface has been investigated using density functional theory slab calculations. Three possible initial steps to decompose methanol by breaking one of three bonds (O-H, C-O, and C-H) of methanol were examined. The relative order of thermodynamic stability for the three possible bond scission steps is C-H > O-H > C-O. We further isolated transition states and determined activation energies for each of the bond-breaking modes using the nudged elastic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…In all the cases, the transition state associated to this process (TS2) involves the reduction of one single Ce 4+ to Ce 3+ , whereas the other unpaired electron resulting from the C-H scission is delocalized over these C and H atoms and the involved surface barrier for the direct formation of I2 from I1 on the (110) was previously reported [38] as 0.9 eV higher than ours. We found that the direct mechanism from I1 to I2 via the transition state TS2 is only favored on the (100) surface.…”
Section: Dehydrogenation Of Methanol To Formaldehyde On Ceomentioning
confidence: 41%
See 1 more Smart Citation
“…In all the cases, the transition state associated to this process (TS2) involves the reduction of one single Ce 4+ to Ce 3+ , whereas the other unpaired electron resulting from the C-H scission is delocalized over these C and H atoms and the involved surface barrier for the direct formation of I2 from I1 on the (110) was previously reported [38] as 0.9 eV higher than ours. We found that the direct mechanism from I1 to I2 via the transition state TS2 is only favored on the (100) surface.…”
Section: Dehydrogenation Of Methanol To Formaldehyde On Ceomentioning
confidence: 41%
“…Despite all the above and other theoretical works reported in the literature [37][38][39][40][41][42], up to date there is no complete study assessing the selectivity of methanol dehydrogenation on the most representative ceria facets and proving their different behavior as experimentally observed. Herein, we present a thorough mechanistic study on the selective conversion of methanol to formaldehyde and its subsequent conversion to CO. To account for the particular morphology of the three common nanoshapes above, we have studied the three lowest index and energy surfaces (111), (110), and (100) (Fig.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, calculations by Mei et al have indicated that the most stable dissociative state on stoichiometric CeO 2(111) involves cleavage of a C-H bond and the formation of a C-O(l) bond [209]. In a subsequent publication these authors indicated that O-H cleavage may be kinetically favored due to much lower activation barrier compared to C-H cleavage, resulting in adsorbed species that agree with experimental observations [210]. The concentration of methoxy on the surface thus determines the number of surface active sites on that surface.…”
mentioning
confidence: 65%
“…Beste et al 70 found two adsorption modes on the perfect (111) surface from DFT+U calculations: molecular and dissociative as methoxy and hydroxyl, with adsorption energies of −0.76 eV and −0.08 eV. Mei et al 71 also used DFT+U to study methanol adsorption at the clean (111) surface. These authors find a coverage dependent adsorption process.…”
Section: Adsorption and Reaction Of Methanol At Ti 2 O 4 -Ceo 2 (111)mentioning
confidence: 99%